2020
DOI: 10.3389/fnhum.2020.00221
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Dynamics of Cortical Neuromagnetic Activity Underlying Seizure Termination in Absence Epilepsy

Abstract: Purpose This study aimed to investigate the spectral and spatial signatures of neuromagnetic activity underlying the termination of absence seizures. Methods Magnetoencephalography (MEG) data were recorded from 18 drug-naive patients with childhood absence epilepsy (CAE). Accumulated source imaging (ASI) was used to analyze MEG data at the source level in seven frequency ranges: delta (1–4 Hz), theta (4–8 Hz), alpha (8–12 Hz), beta (12–30 Hz), gamma (30–80 Hz), ripple (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
(98 reference statements)
1
13
0
Order By: Relevance
“…A previous study on absence seizures demonstrated that during the ictal period, FC networks were more likely to localize in posterior brain regions at low-frequency ranges and localize in anterior regions at high-frequency bands, which was consistent with our results (48). Other studies also found distinct alterations of networks in different frequency bands in CAE patients (13,30,47,49,50). According to a previous report, the types of connections in different frequency bands had specific interactions that allowed information to be integrated or shared at different spatiotemporal levels (48).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous study on absence seizures demonstrated that during the ictal period, FC networks were more likely to localize in posterior brain regions at low-frequency ranges and localize in anterior regions at high-frequency bands, which was consistent with our results (48). Other studies also found distinct alterations of networks in different frequency bands in CAE patients (13,30,47,49,50). According to a previous report, the types of connections in different frequency bands had specific interactions that allowed information to be integrated or shared at different spatiotemporal levels (48).…”
Section: Discussionsupporting
confidence: 92%
“…Another study also found that the cortical regions involved in epileptic networks during seizure termination were wider than those at seizure onset, indicating that the changes in the patterns of FC networks participated in seizure termination (45). Moreover, altered function in the frontal lobe during seizure termination was reported by recent investigations (46,47). Given the literature mentioned above as well as the results found in our study, we speculated that the changes in FC network patterns associated with the frontal cortex were involved in the termination of absence seizures.…”
Section: Discussionmentioning
confidence: 84%
“…The source activity was computed by a wavelet based beamformer and the spatial resolution was 3 mm. The detailed mathematical algorithms and verifications were recently published [26,27] and this method has also been applied in some related studies [28,29]. Thereafter, the functional network of the whole brain was constructed at the source level by calculating the correlation and direction of two source pairs, in 60 seconds.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…where Asi stands for the accumulative source strength at location r, s represents time slice, t represents the time point of MEG data, n stands for the entire time points of MEG data, and Q is the source activity at the time point t and source r. Detailed algorithms were described in the previously published paper (30), and this method has been used in several research (31)(32)(33)(34)(35)(36).…”
Section: Source Localizationmentioning
confidence: 99%